The Urgency of the Constitutional Question by the Constitutional Court and Its Relevance to the Indonesian Democracy Index during the COVID-19 Pandemic - Madjid, Mario Agritama S.W.; Asmorojati, Anom Wahyu (Jurnal Penegakan Hukum dan Keadilan, 2023)
The Constitutional Court’s authority to conduct the judicial review contains deficiencies implied upon the less maximum efforts to actualize constitutional democracy during the COVID-19 pandemic. Hence, the constitutional question is crucial in responding to the issue; it influences the increase of the Indonesian democracy index during the COVID-19 pandemic. The present study aimed to examine and analyze the urgency of constitutional questions by the Indonesian Constitutional Court in actualizing constitutional democracy with a particular design if it is to be regulated in the Constitution and the laws of the Constitutional Court. The research belongs to normative juridical with library research method. The results showed the urgency of the Indonesian Constitutional Court’s authority to impose constitutional questions. (1) It is to increase the Indonesian democracy index during the COVID-19 pandemic (2) It is to protect the citizens’ Constitutional Rights; (3) It is to increase the citizens’ constitutional awareness; (4) It is to connect the judges’ interpretation; (5) It is to actualize progressive and responsive substantive justice. Besides, the research compared the authorities of the constitutional courts applied by countries such as Austria, Germany, and Russia, where the Constitutional Courts in several countries have constitutional question authority. A recommendation of constitutional question arrangement within the Indonesian constitutional system accompanied this research.